LINGUISTIC AND CORPUS MODELING OF “BUILDING-CONSTRUCTION” TERMINOLOGY - Kurbanova Dilnoza Arslonovna; Ibragimova Gulruh Rustam qizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Today, as the construction industry is rapidly developing, in-depth study of its terminological system is gaining both theoretical and practical importance. In particular, construction terms in English play an important role in international cooperation, scientific research and practical projects. This master's thesis is devoted to the topic "Linguistic and corpus modeling of building-construction terminology (on the material of English language)", which provides an in-depth analysis of the theoretical foundations, semantic and structural features of construction terminology, as well as its modeling based on corpus linguistics. The study covers morphological and word-formation models, semantic classification and functional features of construction terms in professional and academic discourse.